UPAYA PENINGKATAN PENGETAHUAN DAN SIKAP IBU-IBU DALAM MENGHADAPI STUNTING PADA BALITA DI DUSUN DONDONG TIMUR II, DESA STABAT LAMA BARAT, KECAMATAN WAMPU, KABUPATEN LANGKAT - Musdalina Musdalina (Jurnal Maternitas Kebidanan, 2020)
The prevalence of stunting in 2007 in asia is 30,6 % .As much as the stunting 37,2 % in indonesia .In southeastern asia prevalence of toddlers stunting in indonesia very high compared myanmar ( % ) 35 , vietnam ( % ) 23 , malaysia ( % ) 17 , thailand and singapore % ) ( 16 .In indonesia , about 37 % ) ( almost 9 million children under five suffer stunting .Toddlers / baduta ( infants under the age of two years ) experienced stunting will have levels of intelligence is not optimal , took the become more prone to illness and the future can risk to the decreasing levels of productivity .Stunting disease is growing on the baby because it has failed to be nutrient .It got the attention of the all the circles to prevent stunting .But , efforts to prevent not be optimal when mothers do not know stunting .The study is done to 100 respondents who are the women having babies .Of 100 respondents , the mothers tend to have related about lack of knowledge , the symptoms , the impact , the cause and prevention .The research uses 2 mothers method of improving knowledge of integrating card and nutritional counseling. This method is the promotion of health who arranged in a decree of the minister of health of the republic of indonesia in 2007